The Effect of Additional Holes and Knurling on Outer Comp Clutch CVT on Torque and Power of Honda Scoopy K93 - Firdaus Audtiya; Rizqi Fitri Naryanto; Abdurrahman; Hanif Hidayat (Jurnal Inovasi Mesin, 2026)
Automatic motorbikes that have been used for more than five years tend to experience a decrease in responsiveness when starting due to wear on the CVT components, one way to improve the performance of automatic motorcycles are to optimize the power distribution from the engine to the wheels. This can be achieved through modifications to the CVT system, so that the power distribution process becomes more efficient and responsive, modifications are made to improve vehicle performance while reducing the impact of decline performance due to increasing age of use, which also has an impact on decreasing CVT performance. On the system CVT, the centrifugal clutch mechanism on the secondary pulley plays a role in connecting and disconnecting rotation from the secondary pulley to the wheel. The component that plays a role in receiving rotation from the clutch carrier is the outer comp clutch, one of the main causes of this problem is the presence of residual dust from the double clutch lining that is trapped inside the outer clutch, which causes slippage and disrupts clutch function. Modification by adding holes and knurling on the surface of the outer comp clutch friction plane is expected to overcome the problem of excessive vibration and slippage, as well as optimizing the performance of the CVT on automatic motorcycles, so that the torque and power produced can increase. The types of knurling applied to the outer comp clutch include straight, diagonal, and diamond knurling